Panax notoginseng Saponins Improve Angiogenesis in Coronary Heart Disease Based on the microRNA 200a Methylation Pathway - Wang J; Dong Y; Li Z; Zhang Y; Liu L; Yang G; Liu Y; Li J; Duan L (Drug Design, Development and Therapy)
Jie Wang, Yan Dong, Zhaoling Li, Yun Zhang, Lanchun Liu, Guang Yang, Yongmei Liu, Jun Li, Lian Duan Department of Cardiology, Guang Anmen Hospital, Beijing, People’s Republic of ChinaCorrespondence: Lian Duan, Email popale2003@163.comBackground: Improving angiogenesis in the ischemic myocardium is a therapeutic strategy for preventing, reducing, and repairing myocardial injury of coronary artery disease (CAD). Panax notoginseng saponins (PNS) have been widely used in the clinical treatment of cardiovascular diseases, demonstrating excellent efficacy, and can potentially improve angiogenesis in the ischemic myocardium. However, the effects of PNS on angiogenesis and its underlying mechanism of action remain unclear.Purpose: In this study, we aimed to evaluate the role of PNS in improving angiogenesis after myocardial infarction (MI) and explain the mechanism of PNS in improving angiogenesis in CAD from an epigenetic perspective.Study Design: The MI rat model was established by ligating the left anterior descending coronary artery permanently. The in vitro model comprised hypoxic human coronary artery endothelial cells (HCEACs). The mice and cells were then treated with PNS.Methods: Blood tests, histomorphology, polymerase chain reaction, enzyme-linked immunosorbent assay, Western blotting, and MassARRAY targeted methylation detection analyses were conducted in vivo and in vitro to investigate the potential mechanisms of PNS.Results: Oral PNS significantly improved myocardial injury and activated angiogenesis in MI rats. DNA methylation analysis in vitro revealed that PNS decreased the hypermethylation of microRNA 200a (miR200a). PNS improved angiogenesis in hypoxic human coronary artery endothelial cells (HCEACs) by regulating the vascular endothelial growth factor (VEGF) pathway.Conclusion: Our research shows that PNS can improve angiogenesis in rats with MI and hypoxic HCEACs and affect the level of miR200a promoter methylation and miR200a and VEGF molecular pathways.Keywords: Panax notoginseng saponins, coronary artery disease, DNA methylation, miRN200a, angiogenesis